Feasibility and Institutional Analysis of Eco-Tourism Development in the Simarjarunjung Area, Dolok Pardamean District, Simalungun Regency - Jawanri Maurisco Saragih; Agus Purwoko; Zulkifli Lubis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Tourism is one of the regional income sectors and can improve the welfare of people's lives. Ecotourism with ecological principles and sustainable development theory will provide benefits by paying attention to the factors that affect it and good management is needed to maintain and continue the development and development of tourism. This study aims to analyze the feasibility of development and institutions in the management of the Simarjarunjung ecotourism area in Dolok Pardamean District, Simalungun Regency. This research is a qualitative descriptive analysis research, where data interpretation and analysis are carried out with data collection steps through documentation techniques as well as interviews and observations, combining relevant information that can answer problems, and drawing conclusions as answers to problems. The results of the feasibility assessment for the development of the potential of the Simarjarunjung Ecotourism Area show a category worthy of development and a feasibility level with an index of 75.74%. The community plays a direct role in ecotourism management for the development of Simarjarunjung ecotourism. The institutional form of ecotourism management is the Association of Farmer Groups (GAPOKTAN) and Tourism Awareness Groups (POKDARWIS). The management of Bukit Indah Simarjarunjung ecotourism is managed privately and the Pine Hills Forest Nature Tourism is managed by the Setya Tani Forest Farmer Group. The strategies carried out in the development of Simarjarunjung ecotourism are planning, implementing, and utilizing. The norms used are internal norms that prioritize local communities and minimize outside participation in the development of Simarjarunjung ecotourism.